Kritik Sosial dalam Novel Maafkan Aku, Kuala Mesuji Karya Fajar: Tinjauan Sosiologi Sastra - Erwin Wibowo (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2018)
Research on novel Maafkan Aku, Kuala Mesuji aims to uncover the social criticism contained in the novel Maafkan Aku, Kuala Mesuji Dawn works through literature sociological approach. The method used in this research is descriptive qualitative method, with which the technical content analysis to uncover and then describe the extrinsic elements, what and how social criticism contained in the novel. The focus of this research is social criticism contained in the novel Maafkan Aku, Kuala Mesuji Dawn works which include: first, social criticism on people's lives Kuala Mesuji. Second, the social criticism of the education in Kuala Mesuji. Engineering analysis conducted by researchers are read and understand the contents of the novel, to analyze social criticism, and then interpret the data according to the indicators focus on research and facts (events) underlying social criticism found. Based on the research results show that the novel Maafkan Aku, Kuala Mesuji works of Dawn, does contain social criticism that is raised from the conversation the leaders and also through the narrative.